Implementation of CHSE Based Health Protocol Policies in Yogyakarta Culinary Tourism - Febryola Indra; Juliana Juliana; Ira Brunchilda Hubner; Deandra Pakasi; Samuel Musa Liha (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Abstract: In order to increase the confidence of tourists and national tourism, the Ministry of Tourism and Creative Economy (Kemenparekraf) has developed a protocol called the Cleanliness, Health, Safety & Environmental Sustainable (CHSE) Protocol in the tourism and creative economy sectors. The research objective is to determine the application of CHSE to the tourism sector and the creative economy, especially in the culinary sector. The type of research used in this study is qualitative. The data collection method in this study was carried out using a literature study or library study, which is a data collection technique carried out by studying the literature and conducting in-depth interviews with culinary tourism actors. Participant taking technique using snowball sampling technique. The result of the research can be identified that the local government has formulated, informed and monitored culinary stakeholders to implement standard health protocols according to predetermined points. According to the CHSE guidelines, the implementation of health protocols for Yogyakarta culinary tourism has been carried out, but there are some minor points that less implemented, but in general the players in the restaurant sector have properly and thoroughly implemented the health protocol based on the CHSE. Keywords: culinary tourism, health protocol, CHSE, Covid-19, Yogyakarta. Abstrak: Dalam rangka meningkatkan kepercayaan wisatawan dan pariwisata nasional, Kementerian Pariwisata dan Ekonomi Kreatif (Kemenparekraf) telah mengembangkan protokol bernama Protokol Kebersihan, Kesehatan, Keselamatan & Lingkungan Berkelanjutan (CHSE) di sektor pariwisata dan ekonomi kreatif. Tujuan penelitian adalah untuk mengetahui penerapan CHSE pada sektor pariwisata dan ekonomi kreatif khususnya pada sektor kuliner. Jenis penelitian yang digunakan dalam penelitian ini adalah kualitatif. Metode pengumpulan data dalam penelitian ini dilakukan dengan menggunakan studi kepustakaan atau studi kepustakaan yaitu teknik pengumpulan data yang dilakukan dengan cara mempelajari literatur dan melakukan wawancara mendalam dengan pelaku wisata kuliner. Teknik pengambilan partisipan menggunakan teknik snowball sampling. Hasil penelitian dapat diidentifikasi bahwa pemerintah daerah telah merumuskan, menginformasikan dan memantau pemangku kepentingan kuliner untuk menerapkan standar protokol kesehatan sesuai dengan poin yang telah ditetapkan. Sesuai pedoman CHSE, penerapan protokol kesehatan wisata kuliner Yogyakarta sudah dilakukan, namun ada beberapa poin minor yang kurang dilaksanakan, namun secara umum para pelaku di sektor restoran telah menerapkan protokol kesehatan dengan baik dan menyeluruh sesuai dengan pedoman yang ada berdasarkan pedoman CHSEKata kunci : wisata kuliner, protokol kesehatan, CHSE, Covid-19, Yogyakarta.